Complete genome sequence of Lelliottia nimipressuralis type strain SGAir0187, isolated from tropical air collected in Singapore - Heinle, Cassie E. (2019)
Lelliottia nimipressuralis type strain SGAir0187 was isolated from tropical air samples collected in Singapore. The genome was assembled with an average coverage of 180-fold using Pacific Biosciences long reads and Illumina MiSeq paired-end reads. The genome measures 4.8 Mb and contains 4,424 protein-coding genes, 83 tRNAs, and 25 rRNAs.